An unresponsive progressive pustular and crusting dermatitis with acantholysis in nine cats. Issue 1 (6th October 2017) - Outerbridge, Catherine A.; Affolter, Verena K.; Lyons, Leslie A.; Crothers, Samantha L.; Lam, Andrea T. H.; Bonenberger, Terri E.; Ihrke, Peter J.; White, Stephen D.
Abstract : Background: Between 2000 and 2012, nine cats were examined with a visually distinctive, progressive crusting dermatitis that was poorly responsive to all attempted therapies. Objectives: Documentation of clinical and histopathological findings of this disease. Animals: Nine privately owned cats. Methods: Retrospective study. Results: Eight neutered males and one (presumably spayed) female ranging in age from two to eight years, presented for a progressive, well‐demarcated, crusting dermatitis with variable pruritus of 1.5 months to five years duration. All cats lived in northern California, USA; seven lived within a 30 mile radius. Two males were littermates. Histopathological investigation showed both parakeratotic and orthokeratotic crusts, intraepidermal pustules and superficial folliculitis with rare to frequent acantholytic cells. Bacterial and fungal cultures were performed in six cats: meticillin‐susceptible Staphylococcus pseudintermedius was isolated in three cats, two colonies of Trichophyton terrestre and three of Malassezia pachydermatis were isolated from one cat each. Treatment with various antibiotics, antifungal and a variety of immunosuppressive medications did not alter the progressive nature of the skin disease. Conclusions and clinical importance: The described disease shares some clinical and histopathological features with pemphigus foliaceus, but the lack of response to treatment, its progressive nature and the possible relatedness of some of the cats set it apart. The aetiology of this acantholytic dermatitis remains unknown. Abstract : Background – Between 2000 and 2012, nine cats were examined with a visually distinctive, progressive crusting dermatitis that was poorly responsive to all attempted therapies.Objectives – Documentation of clinical and histopathological findings of this disease.Conclusions and clinical importance – The described disease shares some clinical and histopathological features with pemphigus foliaceus, but the lack of response to treatment, its progressive nature and the possible relatedness of some of the cats set it apart. The aetiology of this acantholytic dermatitis remains unknown.